2000
DOI: 10.1034/j.1600-0560.2000.027001040.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous collagenous vasculopathy with generalized telangiectasia: an immunohistochemical and ultrastructural study

Abstract: We report a 54-year-old male, with a 5-year history of spreading asymptomatic generalized cutaneous telangiectases. The patient had no mucosal or nail involvement, no positive family history and no clinical evidence of systemic disease or bleeding diathesis. Histologically, the superficial small dermal blood vessels were dilated and showed thickened walls with hyaline perivascular material, staining as collagen. The vessel walls were PAS and colloidal iron stain positive, and immuno-histochemically lacked acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(156 citation statements)
references
References 22 publications
6
142
0
8
Order By: Relevance
“…Electron microscope analysis shows that the affected vessels correspond to postcapillary venules. Around the basal lamina of these venules is deposited a granular material with medium electrodensity within which collagen fibers are irregularly arranged [1,2]. In these fibers transverse bands are observed with anomalous periodicity (Luse bodies) that are not unique to CCV.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Electron microscope analysis shows that the affected vessels correspond to postcapillary venules. Around the basal lamina of these venules is deposited a granular material with medium electrodensity within which collagen fibers are irregularly arranged [1,2]. In these fibers transverse bands are observed with anomalous periodicity (Luse bodies) that are not unique to CCV.…”
Section: Discussionmentioning
confidence: 99%
“…This thickening is due to deposition of eosinophilic material around the endothelial basal lamina showing positivity with PAS staining and is stained blue with Masson trichrome. Mucinous material is often found [1,2,3,4,5,6] in this deposit. It has been reported that collagen IV, fibronectin and laminin are positive [1,2] but in our case No.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations